Artifices of Anastrepha obliqua (Macquart, 1835) (Diptera: Tephritidae) for survival in umbu, endemic fruit from Brazil - Oliveira, Jhonny G.; Bezerra-Silva, Gerane C. D.; Santos Junior, Pedro L.; Luz, Domingas S.; Lopes, Gleidyane N.; Silva, Mácio A. (Entomological Communications, 2022)
We studied the interaction involving umbu, fruit flies and parasitoids in the Brazilian cerrado biome in Piauí state. The fruits were collected in Baixa Grande do Ribeiro and Uruçuí in the period from February to April 2013 and were analyzed in Laboratory. In this study is being published the first occurrence of Anastrepha obliqua (Macquart, 1835) in umbu fruits and two parasitoids, Aganaspis pelleranoi (Brèthes, 1924) and Opius bellus (Gahan, 1930), in Piauí. Where 77.8 % of the fruits were infested by A. obliqua, with 149.4 pupae / kg (2.4 pupae / fruit) and the parasitism rate was 2.7 %. Natural parasitism is not very significant, however, less pupae were found in fruits with parasitized larvae, suggesting that the fly avoids oviposition. Additionally , it was found that the A. obliqua performs multiple oviposition in umbu during host selection and multiple infestations is a factor that increases the likelihood of emergence of A. obliqua during the colonization of umbu. The tritrophic interaction among S. tuberosa, A. obliqua and O. bellus was discussed.